Relative reliability, standard error of measurement and minimal detected change of transabdominal ultrasound during pelvic floor muscles contraction, Valsalva maneuver, and abdominal curl in healthy women - Maedeh Fani; Reza Salehi; Navid Chitsaz; Shahin Goharpey; Shahla Zahednejad (Mashhad University of Medical Sciences, 2020)
Introduction: Transabdominal ultrasound (TAU) is a non-invasive and easy method that can directly evaluate the function of pelvic floor muscles (PFM) through observation of the bladder base movement. Although, studies have investigated the reliability of this technique during PFM contraction, but there is little evidence of reliability during Valsalva maneuver and abdominal curl. This study was performed with aim to assess the reliability, standard error of measurement and minimal detectable change of TAU of PFM activity during contraction, Valsalva maneuver and abdominal curl in healthy women. Methods: This methodological study was performed on 15 volunteer's women (20-45 years) who had no symptoms of urinary incontinence in Kashani hospital of Isfahan in 2018. 15 participated in this study. The bladder base displacement (as an indicator of PFM activity), in millimeters, was assessed by TAU during PFM contraction, Valsalva maneuver, and abdominal curl in two sessions at intervals of a week. Interclass Correlation Coefficient (ICC) and standard error of measurement tests were used to evaluate the reliability, standard error of measurement, and minimal detectable change (significance level=0.05). Results: Reliability of TAU for evaluating the bladder base displacement during PFM contraction was 0.88, during Valsalva maneuver 0.95, and during abdominal curl 0.83. The minimal detectable change during PFM contraction was 2.27 mm, during Valsalva maneuvering 7.94 mm, and during abdominal curl 5.65 mm. Conclusion: Reliability of transabdominal ultrasound in PFM activity assessment during contraction, Valsalva maneuver, and abdominal curl is good to excellent.